On the quantization of sectorially Hamiltonian dissipative systems - Castagnino, Mario Alberto G. J. (2009)
We present a theoretical discussion showing that, although some dissipative systems may have a sectorial Hamiltonian description, this description does not allow for canonical quantization. However, a quantum Liouville counterpart of these systems may be possible, although it may not be unique.